(untitled) (REMUNOM, 2025)
This study investigates how consumers evaluate the quality of services offered in a small supermarket located in Denise, in the state of Mato Grosso. To this end, the SERVPERF instrument was used, structured in five dimensions: reliability, safety, empathy, tangible aspects and responsiveness. A total of 175 customers participated, whose responses were analyzed based on the mean and standard deviation of each item, complemented by a Multidimensional Scaling Analysis (MDS), with the aim of graphically mapping the respondents’ perceptions. The results revealed that the most positive evaluations were concentrated in the “Safety” dimension, especially in items related to the friendliness of employees and trust in service. In contrast, the “Tangible Aspects” dimension presented the lowest average scores, indicating a less favorable perception regarding the physical structure and visual organization of the establishment. The MDS allowed these perceptions to be visually represented, reinforcing the proximity between the best-rated attributes, which suggests convergence in the consumers’ experience. The analysis also identified relevant perceptual clusters, providing support for more focused management actions.By using a quantitative and exploratory approach, this study contributes to the understanding of the shopping experience in local and smaller contexts, where the perception of service quality can strongly influence customer loyalty. It should be noted that the findings refer exclusively to the group studied, and do not allow for generalizations. The combined approach of SERVPERF and MDS proved to be effective in capturing nuances of consumer perception in food retail environments.